2020
DOI: 10.1111/dth.13243
|View full text |Cite
|
Sign up to set email alerts
|

Practical compendium for psoriasis management

Abstract: Psoriasis management is complex and challenging. It should be tailored for each patient. Treatment strategy differs according to patient's age, sex, disease type, disease severity, burden on patient's quality of life, comorbidities, involvement of specific sites, and pregnancy. The choice of the appropriate therapeutic must take into consideration the availability, the price, and the patient's preferences. It is very important that the chosen treatment is not more unpleasant, intolerable, or dangerous than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 61 publications
0
8
0
2
Order By: Relevance
“…However, until very recently, there have been no economic restrictions on the selection of biologic drug once the decision is made to move from conventional to biologic antipsoriatic treatment. Because this may not be the case in other countries, 44 our results offer a nonbiased, real‐world analysis of outcome and the persistence of biologic treatments independent of insurance guidelines. The fact that gender and biologic non‐naïvety affects drug survival rates in a similar fashion for all biologic treatments (independent of the type of drug) may help both patients and clinicians in treatment decision‐making.…”
Section: Discussionmentioning
confidence: 99%
“…However, until very recently, there have been no economic restrictions on the selection of biologic drug once the decision is made to move from conventional to biologic antipsoriatic treatment. Because this may not be the case in other countries, 44 our results offer a nonbiased, real‐world analysis of outcome and the persistence of biologic treatments independent of insurance guidelines. The fact that gender and biologic non‐naïvety affects drug survival rates in a similar fashion for all biologic treatments (independent of the type of drug) may help both patients and clinicians in treatment decision‐making.…”
Section: Discussionmentioning
confidence: 99%
“…Since psoriasis presents subtle inflammation even during remission phases, 19 there was a high level of consensus on the need to provide long‐term proactive topical treatment to reduce the risk of relapse in patients with mild‐to‐moderate psoriasis and prolong time free from disease, in line with current practice in atopic dermatitis 20,21 . Furthermore, according to the Panel, long‐term topical treatment can have a role in the treatment of challenging disease sites on which systemic treatment is often not fully effective, such as the hands, elbows, and scalp 22,23 . In addition, according to the Panel, topical long‐term proactive treatment of psoriasis can be useful when phototherapy or systemic treatment are contraindicated or ineffective, two conditions that may be frequently encountered in clinical practice 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…According to the international consensus decision, moisturizers and low-medium potency corticosteroids are recommended as the fi rst option in the treatment of psoriasis during pregnancy [7,49]. While the uses of topical high potency steroids and topical calcipotriol are not recommended in this period, these topical agents can be used especially from the 3rd trimester [50][51][52][53][54].…”
Section: Pregnancy Course In Patients With Psoriasismentioning
confidence: 99%
“…Methotrexate is one of the wellknown agents that should be avoided both during pregnancy and lactation due to its mutagenic, teratogenic and abortogenic properties. Psoralen + Ultraviolet A (PUVA) therapy should also not be preferred during both pregnancy and lactation due to mutagenic potential of psoralens [7,9,[51][52][53][54]. However, it has been suggested that topical PUVA therapy for palmoplantar psoriasis may be relatively safer, especially from the 3rd trimester [9].…”
Section: Pregnancy Course In Patients With Psoriasismentioning
confidence: 99%
See 1 more Smart Citation